2020
DOI: 10.1097/dss.0000000000002642
|View full text |Cite
|
Sign up to set email alerts
|

Modified Buried Vertical Mattress Suture Versus Buried Intradermal Suture: A Prospective Split-Scar Study

Abstract: BACKGROUND The modified buried vertical mattress suture (MBVMS) is believed to provide excellent outcomes by relieving the tension on wound edges. However, clinical data on the topic remain sparse and inadequate. OBJECTIVE To compare the cosmetic results of the MBVMS and the buried intradermal suture (BIS) in chest wounds using a split-scar model. MATERIALS AND METHODS Twenty patients participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The modified buried vertical mattress suture (heart-shaped suture) is currently commonly used in obstetrics and other professions, and is gaining popularity in orthopedics, but its biomechanical benefits are rarely reported [ 27 ]. Because of the larger bite of dermis in a single stitch, its decompression effect should be superior to that of the intradermal buried vertical mattress suture (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified buried vertical mattress suture (heart-shaped suture) is currently commonly used in obstetrics and other professions, and is gaining popularity in orthopedics, but its biomechanical benefits are rarely reported [ 27 ]. Because of the larger bite of dermis in a single stitch, its decompression effect should be superior to that of the intradermal buried vertical mattress suture (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 6 Cross-sectional view depicting the modified buried vertical mattress suture (heart-shaped suture) before (a) and after (b) knotting and the buried intradermal suture before (c) and after (d) knotting [ 27 ]
…”
Section: Discussionmentioning
confidence: 99%
“… 33 The premise of WE-MBVMS is that wedge-shaped excision is performed first and then the needle is inserted in the subcutaneous tissue obliquely, enters the middermis repeatedly along an arc track, and involves the dermis as much as possible (Figure 3 D). 34 Current clinical trials have verified its good cosmetic effect and safety in high-tension wound closure. Liu's split-scar model showed that WE-MBVMS significantly increased wound eversion both immediately and postoperatively and performed significantly better on the scar assessment at the end of the 3-month follow-up period than intradermal buried sutures.…”
Section: Methodsmentioning
confidence: 99%
“…Liu's split-scar model showed that WE-MBVMS significantly increased wound eversion both immediately and postoperatively and performed significantly better on the scar assessment at the end of the 3-month follow-up period than intradermal buried sutures. 34,35 Similar to other subcuticular sutures, it is not useful for extremely thin dermis or tiny wounds. [19][20][21] Set-Back Suture Another super-tension-reduction suture was invented by Kantor in 2010, namely, the set-back suture.…”
Section: Wedge-section and Modified Buried Vertical Mattress Suturementioning
confidence: 99%
“…To the Editor, To reduce dead space, inhibit scar hyperplasia, and improve aesthetic outcomes, modified buried vertical mattress sutures 1 are commonly used to close wounds. However, the method is most suitable for suturing low-tension wounds.…”
Section: Multi-gradient Buried Vertical Mattress Suture An Effective ...mentioning
confidence: 99%